The Cost of Decentralization: Linguistic Polarization and the Provision of Education - Francesco Cinnirella; Ruth Maria Schueler (Center for Economic Studies and ifo Institute (CESifo), 2016)
In this paper we argue that different preferences in a decentralized system lead to under provision of public goods. We analyze the provision of public primary education in nineteenth-century Prussia which was characterized by a linguistically polarized society and a decentralized education system. Using unique county-level data on education spending we show that linguistic polarization has a negative impact on local spending. Instrumental variable estimates using distance to the eastern border suggest that the relationship can be causally interpreted. Exploiting a reform of education spending, we show that centralization increases the provision of primary education relatively more in linguistically polarized counties.
Keywords: H41; H75; I22; N13; N33; 330; education; public goods; polarization; decentralization; centralization; Prussia